Hyperhidrosis in Parkinson's disease: a 3‐year prospective cohort study. (23rd March 2022) - Lin, J.; Ou, R.; Wei, Q.; Cao, B.; Li, C.; Hou, Y.; Zhang, L.; Liu, K.; Shang, H.
Abstract: Background: Although hyperhidrosis is a common symptom in patients with Parkinson's disease (PD), no study has yet examined it longitudinally. Objectives: We conducted a 3‐year prospective cohort study to investigate the development, evolution and correlates of hyperhidrosis in patients with PD. Methods: A total of 224 patients with early‐stage PD were enrolled at baseline and followed up annually for three consecutive years. Hyperhidrosis was assessed using hyperhidrosis question (item 30) of the Non‐Motor Symptoms Scale (NMSS). The generalized estimating equations model was applied to investigate the correlates of both presence and severity of hyperhidrosis. Results: The frequency of hyperhidrosis in PD had an overall increasing tendency from 24.1% at baseline to 34.4% after 3 years, although hyperhidrosis was not always persistent in all patients over the 3‐year study period. The presence of hyperhidrosis was found to be associated with dyskinesia (OR 2.27 [1.02–5.04], P  = 0.045), the sexual function domain subscore of the NMSS (OR 1.04 [1.01–1.07], P  = 0.016), the Hamilton Anxiety Rating Scale (HARS) score (OR 1.08 [1.03–1.13], P  = 0.001) and the Unified Parkinson's Disease Rating Scale part III score (OR 1.02 [1.00–1.04], P  = 0.036). Only the HARS score was associated with the severity of hyperhidrosis (B 0.08 [0.03–0.12], P  = 0.001). Conclusions: Hyperhidrosis is common in PD, and its frequency increases along with disease duration. Hyperhidrosis in PD is associated not only with motor severity and motor complication such as dyskinesia, but also with non‐motor symptoms such as sexual dysfunction and anxiety.